Enemy of my dreams - Williamson, Jenny (Podcaster) (Canary Street Press, 2025)
"In the last days of the Roman Empire, a desperate princess and a brutal Gothic warlord forge a dangerous alliance. Julia, only daughter of the emperor of Rome, lives a life of excess and freedom. Wine, philosophy, and scandal--she revels in hedonism. But when her father dies and her teenage brother takes the throne, he will stop at nothing to seize control of both the empire and his wayward sister. And now Alaric of the Visigoths, a ferocious warrior who has battled Rome for years, has come to the capital to bargain for his homeland. When Julia rebels against the marriage her brother has ordered her to accept, he responds by publicly punishing her lover in the Colosseum. Realizing how perilous her position is, Julia impulsively turns to Alaric--the empire's sworn enemy, and the one man who can make Rome tremble. Julia must find a way to make an ally of Alaric, a man she can't trust--a terrifying warlord with the power to bring both Julia and the empire to their knees--in an edgy, sexy cat-and-mouse game of attraction, defiance, and lust"--